Assessment of Dapitan City’s Tourism Resources: Basis for the Development of Tourism Plan - Pallega, Lovelle (International Journal of Scientific Research and Management (IJSRM), 2022)
Recognizing the role of tourism in achieving the sustainable development goals, the local government unit of Dapitan City aims to unlock its potential and opportunities through its tourism development plan. As an initial step, this study was conducted to assess the tourism resources of Dapitan City. A mix of quantitative and qualitative approaches were employed in gathering the data which includes a series of focus group discussions (with the different stakeholders) site evaluation survey, informal interviews, site visits and data mining of secondary data. The findings revealed that Dapitan City is endowed with rich natural and cultural heritage which are its greatest assets in promoting tourism. Most of the tourism sites are accessible and have good quality of surroundings but have poor basic utilities and onsite facilities available. Market demand is high from domestic visitors but low in terms of foreign markets. The number of tourism enterprises is limited in relation to demand. Despite being tagged by the negative image of the name “Zamboanga”, Dapitan City remains to be one of the safest places to visit. Therefore, tourism industry if properly planned and managed has the ability to stimulate local economic growth, social welfare, and preserve the natural and cultural resources of the city. The study recommends that future developments in tourism shall be focused on the niche of ecotourism, heritage tourism and agritourism.